2020
DOI: 10.3390/ijms21249756
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde-3-Phosphate Dehydrogenase Increases the Adhesion of Lactobacillus reuteri to Host Mucin to Enhance Probiotic Effects

Abstract: The ability to adhere to the intestinal mucus layer is an important property of probiotic bacteria. Lactobacillus reuteri strains ZJ615 and ZJ617 show low and high adhesion, respectively, to intestinal epithelial cells. In this study, we quantified bacterial cell wall-associated glyceraldehyde-3-phosphate dehydrogenases (cw-GAPDH) and bacterial cell membrane permeability in both strains using immunoblotting and flow cytometry, respectively. Highly adhesive L. reuteri ZJ617 possessed significantly more cw-GAPDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…13,63−67 Although mechanisms underlying the beneficial effects of heat-inactivated probiotics remain inconclusive, the consistently observed benefits of inactivated probiotics may be attributed to the microbial metabolites. 7,14,15,68 Here, we found that adding PKP in the culture medium successfully augmented protective effects of pasteurized L. reuteri against HFHS-induced liver injury, impaired hepatic lipid metabolism, and gut dysbacteriosis, which were superior to PKP per se and the cosupplementation of live L. reuteri and the heat-inactivated L. reuteri cultured by MRS. These benefits may be attributed to the PKP per se and its promoted metabolites of L. reuteri (e.g., propionic acid, indole derivatives, phenyllactic acid, succinic acid) exerting health-promoting effects, which could also prominently prevent gut dysbacteriosis and increase SCFA production.…”
Section: Discussionmentioning
confidence: 69%
“…13,63−67 Although mechanisms underlying the beneficial effects of heat-inactivated probiotics remain inconclusive, the consistently observed benefits of inactivated probiotics may be attributed to the microbial metabolites. 7,14,15,68 Here, we found that adding PKP in the culture medium successfully augmented protective effects of pasteurized L. reuteri against HFHS-induced liver injury, impaired hepatic lipid metabolism, and gut dysbacteriosis, which were superior to PKP per se and the cosupplementation of live L. reuteri and the heat-inactivated L. reuteri cultured by MRS. These benefits may be attributed to the PKP per se and its promoted metabolites of L. reuteri (e.g., propionic acid, indole derivatives, phenyllactic acid, succinic acid) exerting health-promoting effects, which could also prominently prevent gut dysbacteriosis and increase SCFA production.…”
Section: Discussionmentioning
confidence: 69%
“…These infants were also enriched for 16S rRNA dimethyltransferase, which confers aminoglycoside resistance, providing evidence for intergenerational transmission of antimicrobial resistance. Infants without detectable IgE at 12 months possessed microbiomes encoding glyceraldehyde-3-phosphate dehydrogenase, which increases Lactobacillus adhesion to host intestinal mucins, 43 and streptomycin biosynthesis, a microbially derived aminoglycoside active against aerobic pathogenic bacteria, 44 suggesting that heritable vaginal bacteria associated with atopy protection may colonize and shape microbial colonization in the developing gut microbiome. These infants also housed heritable bacteria capable of histamine and tryptophan degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Among Lactobacillus species, adhesive properties are extremely strain-specific and depend on the presence of specific adhesion factors 6,7,23,[36][37][38][39] . The finding that L. rhamnosus ATCC 53103 was unable to bind mucins correlates with a previous study indicating that some L. rhamnosus strains isolated from different formulations were www.nature.com/scientificreports/ severely compromised in mucin-binding ability 40 .…”
Section: Discussionmentioning
confidence: 99%